Comparison of Antimicrobial Treatment Incidence Quantification Based on Detailed Field Data on Animal Level with the Standardized Methodology of the European Medicines Agency in Veal Calves, Switzerland, 2016-2018 - Jens Becker; Mireille Meylan (MDPI AG, 2021)
Precise quantification of antimicrobial treatment incidence (TI) is crucial for benchmarking. Two widespread methods for treatment incidence quantification were compared for agreement. Field data were obtained from 38 veal farms from 2016 to 2018 (1905 calves, 1864 treatments). Calculation of TIswiss for calves was based on detailed treatment records using pharmacokinetic values from the Swiss Veterinary Medicines Compendium. The method published by the European Medicines Agency was used to calculate TI in defined daily doses (TIDDD). For each calf and treatment, TIswiss and TIDDD were calculated on level of the antimicrobial class, drug, application route, and farm. The quotient (Q) of TIswiss and TIDDD was calculated. Divergence in results between the two methods of ≤25% was arbitrarily set as good agreement. The agreement between TIswiss and TIDDD was mostly good. On class level, good agreement was observed for treatments representing 71.5% of the TIDDD, and 74.5% of the total TIDDD on drug level. Poor agreement was mainly observed for tylosin and sulfadimidine. The agreement was better for parenteral than for oral treatments (81.6% vs. 72.3%). For practically orientated calculation on farm level, good agreement was observed (77.5% of the TIDDD). The TIDDD method showed mostly good agreement, especially for parenteral treatments.